2020
DOI: 10.1371/journal.pone.0241628
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and hypertension: A systematic review and meta-analysis

Abstract: Background Food insecurity (FIS) is an important public health issue associated with cardiovascular risk. Given the association of FIS with diets of poorer nutritional quality and higher salt intake as well as chronic stress, numerous studies have explored the link between FIS and hypertension. However, no systematic review or meta-analysis has yet to integrate or analyze the existing literature. Methods We performed a wide and inclusive search of peer-reviewed quantitative data exploring FIS and hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 75 publications
2
34
1
2
Order By: Relevance
“…SMD metaanalyses found no significant differences in FBG or HbA1c levels between food insecure and food secure adults. Instead, similar to a prior review by the authors, 22 this study demonstrated that FIS is specifically associated with increased self-reported T2DM among adults. For paediatric patients, SMD meta-analysis found no significant difference in HbA1c levels between paediatric patients with and without FIS.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…SMD metaanalyses found no significant differences in FBG or HbA1c levels between food insecure and food secure adults. Instead, similar to a prior review by the authors, 22 this study demonstrated that FIS is specifically associated with increased self-reported T2DM among adults. For paediatric patients, SMD meta-analysis found no significant difference in HbA1c levels between paediatric patients with and without FIS.…”
Section: Discussionsupporting
confidence: 88%
“…Second, the majority of the studies cited involved a self-reported diagnosis (rather than a clinically determined one), a confounding factor identified in other meta-analyses related to FIS, 22 The findings of our review also contrast with two additional recent systematic reviews by da Silva Miguel et al 87 and Vazquez et al 88 , both of which were identified during the review process and concluded that FIS is associated with T2DM. However, we note that (a) neither study included meta-analyses; (b) these reviews did not distinguish between self-reported versus clinically determined T2DM; and (c) Vazquez et al relied heavily upon the findings of Abdurahman et al in making their conclusions, without the addition of other available data.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, no meta-analysis was performed, and some of these studies used self-reported dyslipidemia. A recent review by Beltran et al 57 showed that most studies in the USA that indicate a correlation between food insecurity and hypertension correspond to self-reporting of conditions. They stated that a likely anxiety connection complicates the relationship between self-reported metabolic risk factors and food insecurity (since anxiety is also increased in food-insecure patients) 58 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, an estimated one in ten people were exposed to severe food insecurity worldwide [ 40 ]. Further, findings from systematic reviews indicate that food insecurity is associated with a higher risk for incident hypertension, type 2 diabetes, and CVD, as well as greater cardiovascular mortality [ 41 45 ]. Certain groups of SGM adults, including lesbian women and bisexual and transgender adults, have higher rates of poverty compared to their non-SGM counterparts, which may increase their risk for food insecurity [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%